Sisterhood in Digital Literacy: Strengthening Women's Resilience Against Online Gender-Based Violence (OGBV) - Yuliarti, Monika Sri; Tri Rejeki , Andayani; Chatarina Heny Dwi , Surwati (Mediator: Jurnal Komunikasi, 2025)
Online gender-based violence (OGBV) continues to rise globally, that gives a negative impact on marginalized groups, including women. Although digital literacy initiatives aim to create safer online spaces, their reliance on individualistic and technocentric models leaves social and structural harms unaddressed. To address these gaps, this article adopts an integrative literature review approach to examine how digital literacy, feminist sisterhood, and collective resilience intersect in forming a more inclusive response to OGBV. This study identifies several limitations in current digital literacy programs, including a limited focus on gender perspectives, a lack of peer-based learning structures, and low participation among at-risk women. Synthesizing the intersection of digital literacy, OGBV, feminist sisterhood, and resilience, this article proposes Collective Digital Empowerment as a conceptual framework that integrates three key aspects: capacity, care, and community. It is expected that a feminist-based and community-involved approach will not only equip women to tackle digital risks but also empower them in their interactions in digital spaces. This way, women can be aware and exercise their agency in digital spaces, rather than enduring unfair and patriarchal environments. By centering sisterhood in digital resilience strategies, this framework offers a more sustainable and justice-oriented approach to combating OGBV.